1996
DOI: 10.1159/000244322
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Nitric Oxide: Effect on Cerebral Hemodynamics and Activity, and Antioxidant Status in the Newborn Lamb

Abstract: Ventilation with nitric oxide (NO) is increasingly being used to treat pulmonary hypertension in the newborn. In the brain, NO has vasoactive properties and is involved in neurotransmission. However, the effect of inhaled NO on the cerebral blood flow (CBF) and on the cerebral activity is not known. Furthermore, there is little information on the influence of this free radical gas on the redox status in pulmonary vessels. We therefore investigated the effect of inhaled NO (2–60 ppm) on CBF, cerebral activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Baseline values of all variables before the exchange transfusion were within the normal range [8]. The blood pressure-related changes in Q car we observed during exchanging blood in this animal study were in accordance with the findings in an earlier study we performed in newborn infants [3].…”
Section: Discussionsupporting
confidence: 92%
“…Baseline values of all variables before the exchange transfusion were within the normal range [8]. The blood pressure-related changes in Q car we observed during exchanging blood in this animal study were in accordance with the findings in an earlier study we performed in newborn infants [3].…”
Section: Discussionsupporting
confidence: 92%
“…Especially, MDA levels were not increased, suggesting that increased lipid peroxidation did not occur. Cardozo et al [21] found similar results in full-term newborn lambs after shortterm exposure (20-30 min) to various concentrations of inhaled NO -2, 4, 10, 20 and 60 ppm. NO reacts readily with sulfhydryl to form nitrosothiols.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, there is growing evidence that iNO might be protective in reducing ischemiareperfusion injury within mesentery (Fox-Robichaud et al, 1998), and myocardium (Nagasaka et al, 2008), thus reducing tissue damage. While experimental (Rosenberg et al, 1995;Lopes Cardozo et al, 1996;Kusuda et al, 1999) and clinical (Vavilala et al, 2001) studies could not detect changes in CBF during iNO therapy, one experimental study revealed that while it did not alter cerebral perfusion, iNO was shown to possess a cerebrovascular effect (Kuebler et al, 2003). Nitric oxide inhalation is a clinically approved treatment that has few side effects that might positively influence the outcome following ischemic stroke.…”
Section: Inhaled Nitric Oxide Donorsmentioning
confidence: 99%